Pierre’s Rational and Public Beliefs - Victor Verdejo (Principia: An International Journal of Epistemology)
Paradigmatic cases of disagreement seem not to be compatible with a widespread kind of solution to Kripke’s celebrated Pierre puzzle. As a result, the classical puzzle about rational belief is shown to be also a puzzle about public disagreement/agreement phenomena. In this paper, I defend that the new public version of the puzzle is substantial and challenging and conclude that a full solution to Kripke’s considerations must offer a satisfactory account of both the rational and public character of belief attributions. I then argue that a notion of non-belief-individuating understanding is plausibly the key notion that would allow us to arrest both versions of the Pierre puzzle.